A full-polarimetric GPR system and its application in ice crack detection. Issue 1 (February 2021) - Li, Xiaotian; Feng, Xuan; Liang, Wenjing; Xue, Cewen; Zhou, Haoqiu; Wang, Ying
Abstract: The warming season of Antarctica, where sea ice melts and breaks, is often the golden time for Antarctic research. But this season is also a high frequency season for the formation of ice crack, the existence of which poses a serious threat to Antarctic scientific research. Therefore, it is of important significance to monitor the trend, location, and depth of Antarctic sea ice crack in real time. Ice crack detection often uses ground penetrating radar (GPR) technology. Compared with the single-polarimetric GPR, full-polarimetric GPR can obtain more comprehensive polarization information. Therefore, a full-polarimetric GPR system based on the horn antenna is built in this paper to obtain more abundant ice crack information. Then we apply it to detect a small-scale ice crack atop frozen lakes. The analysis of the experiments and data fusion processing results can verify the effectiveness of the system for the detection of ice crack and lay the foundation for subsequent actual detection.